Evaluation of the Impact of IND AS 113 Fair Value Measurement on Financial Statements - Gupta, Ambrish (Indian Journal of Finance, 2018)
Fair value is the mantra of today in financial reporting across borders. In India also, the Institute of Chartered Accountants of India (ICAI) converged its accounting standards with IFRSs and accordingly, corporate financial statements beginning accounting year 2016-17 started disclosing financial figures based on fair value measurement. One of the purposes of fair value measurement is to narrow the gap between balance sheet value and market value of a company. Fair value measurement aims at fair recording of a business transaction so that the financial statements are able to show a true and fair view of the profitability and financial position. Fair value measurement can be applied to different elements of financial statements. I put this measurement basis to test through a case with reference to fair value mechanism applicable to purchase of current investments and their continuing holding on the balance sheet date. The results clearly supported the philosophy behind the fair value measurement basis. To sum up, it was found that the FV measurement does away with window dressing, makes the financial statements more transparent, closer to real market value, less volatile, and more predictable in accordance with the principle of substance over form, which is becoming all pervasive now.